DEVELOPING READING I MATERIALS BY INTEGRATING READING AND PEDAGOGICAL SKILLS FOR ENGLISH LANGUAGE EDUCATION STUDENTS OF UNIVERSITY OF POTENSI UTAMA - Winda Syafitri; Nur'afifah Hasbi Nasution (Journal MELT (Medium for English Language Teaching), 2019)
Content-Based Instruction (CBI) is a very good concept to apply in any class including English Language Education class. Teaching language skills by having certain content is one of what CBI does. This research aims at developing Reading I materials by integrating reading skill and pedagogical knowledge for English Language Education students of University of Potensi Utama. It applied Research and Development (R&D) which dealt with some stages: needs analysis, review of literature, product development, expert validation, try out and dissemination. The result of this research is a set of text book of Reading I Materials containing pedagogical content which can be used in English Language Education of University of Potensi Utama. After try out, students who were respondents of this research said that Reading I materials developed by integrating reading and pedagogical skills are very interesting and useful because it relates to their interests and add their knowledge on English language teaching.